Curcuma longa L. Prevents Hepatotoxicity Induced Isoniazid and Rifampicin: An Experiment in Wistar Rats Model - Rahman, Putri Halleyana; Dwiwina, Resti Gradia; Pratiwi, Yuni Susanti; Bashari, Muhammad Hasan (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Hepatotoxicity induced by the combination of isoniazid (INH) and rifampicin (RIF) in the treatment of tuberculosis (TB) remains a major concern. Oxidative stress has a role in mechanism of hepatotoxicity. Curcuma longa L. has been widely used as a traditional medicine and has shown antioxidant activity. This study aimed to provide evidence of Curcuma longa L as protection against oxidative stress induced by isoniazid and rifampicin therapy.Methods: This was an experimental study on male Wistar rats weighing 150-200 grams, aged 8-10 weeks which were divided into a negative control group (K0), a positive control group with INH + RIF (K1), a treatment group with a dose of 2.2 gr/kg/day Curcuma longa L powder (K2), and treatment group with INH+RIF and additional 2.2 gr/kg/day turmeric rhizome powder (K2+). SGOT and SGPT were measured from blood plasma on the 28th day; then hepatic tissue was obtained to measure MDA levels and observed histologically. Statistical analysis was done using ANOVA and continued with Duncan procedure using SPSS ver. 27.Results: SGOT, SGPT, the highest average MDA level in the liver, and the highest mean necrotic cell count in the positive control group showed a significant difference (p<0.05). The treatment group had a smaller average number of necrotic cells than the positive control group with a significant difference (p <0.05).Conclusion: Curcuma longa L powder has been shown to prevent elevation in SGOT, SGPT, MDA of liver tissue and hepatocyte necrosis, indicating its potential in protecting the liver from oxidative stress.